Pengembangan Ekonomi Indonesia Berbasis Wisata Halal - Fitrianto, Fitrianto (BISNIS, 2019)
This paper describes the development of Indonesian economy based on halal tourism. The tourism sector is Indonesia's mainstay in gaining foreign exchange. Tourism can be used as an engine of economic growth for the country. The Indonesian government targets 20 million foreign tourist visits in 2019. Foreign tourist visits to Indonesia have increased during 2017 to 2018. The Badan Pusat Statistik (BPS) released the number of foreign tourist visits to Indonesia during 2018 to reach 15.81 million or an increase of 12.58%. In 2018, foreign exchange from the tourism sector accounted for US $ 17 M, an increase of 11.8%.Halal tourism is a tourism concept that matches Islamic values. Indonesia has a great opportunity in developing the halal tourism sector. Bank Indonesia (BI) states that halal tourism also supports the development of Islamic economics. Halal tourism can strengthen the country's economy. In April 2019 Indonesia was ranked first in the category of the world's best halal tourism destinations based on the Global Muslim Travel Index (GMTI) standard.